Conceptual framework: The role of cognitive absorption in delone and mclean success model in online learning in United Arab Emirates - Alketbi, Sareea; Akmal, Suriati; Abdul Hamid, Rahimah; Al-Shami, Samer Ali Hussein (Allied Business Academies, 2021)
As COVID-19 pandemic has taken the world by surprise, it has resulted in an alteration to human activities that have never been seen before. Among the many areas that have been mostly affected is the education industry where institutions have resorted to online learning to maintain the educational process during lockdowns and other strict measures that governments around the world have implemented. Performance impact of such technology has risen as the main concern in that context; this study is making use of Delone & Mclean information success model to examine performance impact of online learning with the addition of cognitive absorption as a moderating variable to come out with a proposed conceptual framework for future empirical undertaking. The intended context of this study will be students within the public universities in the United Arab Emirates and implications are thoroughly discussed as well.